Physical performance tests and anthropometric data to predict selection in U19 rugby union players - Vaz, L.; Batista, M.; Honório, S.; Fernandes, H. M. (Journal of Human Sport & Exercise, 2019)
Anthropometric and performance data were collected from 184 rugby players (mean age=17.9±0.5 years, body mass=84.2±13.5 kg; height =1.79±0.07 m) to explore: (i) the correlation among indicators; and (ii) compare profiles from the selected (n =39) and non-selected (n =145) players to represent the Portuguese under-19 national team. Anthropometry characteristics included body height and body mass. Physical performance variables included push up and pull-up test, squat, Sargent test, flexed arm hang test, sit-and-reach test, 20 m shuttle run test, handgrip strength test, 20-m and 50-m sprint and Illinois agility test. The results showed that the selected rugby athletes reported significantly higher levels of right (t = 2.77, p = 0.01, ES= -0.5 [-0.8 to -0.2]) and left handgrip strength scores (t = 2.81, p = 0.01, ES = -0.5 [-0.8 to -0.2]), and significantly better (i.e. lower) levels of agility scores (t = -2.28, p = 0.02, ES = 0.4 [0.1 to 0.7]) than the non-selected rugby athletes. Accordingly, prospective players need to be constantly monitored and evaluated across age-categories in order to allow them to achieve the anthropometrical and fitness requirements needed to play at the international level.